2020
DOI: 10.1002/jhet.3902
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between Suzuki cross‐coupling reaction and direct arylation in the synthesis of new antibacterial imidazo‐pyrazines/pyridazines

Abstract: Two efficient synthetic routes to preparation of 2,3‐diarylimidazo[1,2‐a]pyrazines and 2,3‐diarylimidazo[1,2‐b]pyridazines are described. The procedures involve a Suzuki cross‐coupling reaction and a palladium‐catalyzed direct arylation at position 3 and finally a comparative study is achieved. The antibacterial activities of the synthesized compounds in vitro were measured and the results showed that most products presented moderate to good antibacterial activities. Compounds 3a, 3c, 3j, 3k, 3l, and 3n reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Reportedly, Pd NPs have been successfully used in C-C coupling reactions in the composition form with other materials and in nano scale. 35 For instance, we have executed this approach by using poly 4-vinylpyridine polymeric substrate and iron oxide magnetic nanoparticles. 36 Biphenyls, as one of the most important pharmaceutical compounds are synthesized via C-C coupling approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reportedly, Pd NPs have been successfully used in C-C coupling reactions in the composition form with other materials and in nano scale. 35 For instance, we have executed this approach by using poly 4-vinylpyridine polymeric substrate and iron oxide magnetic nanoparticles. 36 Biphenyls, as one of the most important pharmaceutical compounds are synthesized via C-C coupling approach.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, designing novel catalytic systems including Pd NPs has found great importance and attracted so much attentions because Pd plays a key role in C-C couplings. 35,41,42 In this regard, we intend to introduce a novel designed Pd-containing catalytic system for the convenient synthesis of biphenyl derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison between Suzuki-Miyaura coupling reaction and direct arylation at position 3 of imidazo[1,2-b]pyridazines was recently performed by Salek Soltani et al. [117] under direct arylation conditions [bromobenzene 1 equiv, Pd-(OAc) 2 5 mol %, PPh 3 0.5 equiv, 1 equiv, K 2 CO 3 (3 equiv), DMA, 130°C, 24 h], provided the desired product 102 in 56 % isolated yield (Scheme 49). Authors have shown that the direct arylation proceeded in general with lower yields than the Suzuki-Miyaura pathway.…”
Section: Functionalization By C-h Activation: Direct Arylation and Benzylationmentioning
confidence: 99%